Zentrale unternehmensfunktionen für wettbewerbs‐ und kundenorientierte prozessläufe - Duttine, André; Ginevičius, Romualdas (Journal of Business Economics and Management, 2003)
Internationalization of economics has become an issue of top priority. This process enhances risks for the companies. With the formation of the European economic zone a number of suppliers has considerably grown. This environment is not friendly for developing small and medium‐size businesses because of not sufficient competitiveness of their products. Competitiveness may be achieved only if the appropriate strategies are pursued. Use of Workflow and management database systems is one of the promising strategies aimed to achieve higher efficiency. This refers both to trade and manufacture, being even more relevant for servicing enterprises. The introduction of standardized technologies can accelerate the dissemination and extension of knowledge in the future. Consistent implementation of the strategies at an enterprise means to perform the behavior oriented function. IT management model offers a possibility to pursue the strategies of getting benefits and differentiation. The emerging mixed strategy embraces both the realization of benefits achieved by Economics of Scope and differentiation benefits obtained by varying the particular products and services. A case study of the particular competitiveness strategy is provided to show how it can realize the identified features of products and services in various areas.Article in German.First Published Online: 14 Oct 2010